Genetically engineered exosomes for targetedly preventing premetastatic niche formation and suppressing postoperative melanoma lung metastasis. (October 2022) - Han, Xiaoqing; Bi, Luopeng; Wu, Yunyun; Yan, Jiao; Wu, Xiaqing; Zheng, Runxiao; Sun, Yingying; Zhang, Hua; Wang, Zhenxin; Wang, Yanbo; Zhang, Haiyuan
Abstract: Premetastatic niche (PMN) is a prerequisite for initiation of tumor metastasis. Targeting prevention of PMN formation in distant organs is becoming a promising strategy to suppress metastasis of primary tumor. Based on "organotropic metastasis", melanoma tends to metastasize to lungs, where granulocytic myeloid-derived suppressor cells (G-MDSCs) recruitment in lungs significantly contributes to the PMN formation. Herein, functional exosomes (G Exo I ) were designed to present pulmonary targeting peptide GFE1 on the membrane and load PI3Kγ inhibitor (IPI549) inside, aiming at suppressing postoperative lung metastasis of melanoma. In postoperative mice model, intravenously injected G Exo I could significantly accumulate in lungs and release IPI549 to block G-MDSCs recruitment through interfering with CXCLs/CXCR2/PI3Kγ signaling. The increased percentages of CD4 + T cells and CD8 + T cells in lungs could transform microenvironment from immunosuppression to immunostimulation, leading to metastasis inhibition. This study suggests an effective anti-metastasis strategy of targeting prevention of PMN formation through specifically blocking G-MDSCs recruitment. Graphical Abstract: ga1 Highlights: Premetastatic niche (PMN) is a prerequisite for initiation of tumor metastasis. G-MDSCs play a vital role in PMN formation. G Exo I targetedly prevents PMN formation by blocking G-MDSCs recruitment. G Exo I transforms lung microenvironment from immunosuppression to immunostimulation. G Exo I suppresses postoperative melanoma lung metastasis.